Perbandingan Legislasi Hukum Pidana Islam Di Indonesia dan Beberapa Negara Muslim Lainnya - Haliza Nur Madhani; Maulina Maulina; Muhammad Wildan; Surya Sukti (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
Islamic criminal law is one part of Islamic law that originates from the Qur’an, Hadith, and ijtihad of scholars. Legislation of Islamic criminal law in terms of its application, there are pros and cons responses from the public in countries that adhere to a secular legal system. In Indonesia, Islamic criminal law legislation is not universally applied, but there are several aspects and provisions that have been accommodated into positive law, and only applied in areas with certain special autonomy authority, such as Aceh. In several Muslim countries, Islamic criminal law is strictly and thoroughly applied, namely in Saudi Arabia, Iran, Libya, Pakistan, and Sudan. In addition, some other Muslim countries that apply Islamic criminal law flexibly are Malaysia, Egypt, Syria, Iraq, Jordan, Tunisia, and Algeria. The purpose of this research is to analyze the legislation of Islamic criminal law in Indonesia and Muslim countries. The research method used is qualitative method by conducting literature study on various sources and relevant data. The result of the research shows that the legislation of Islamic criminal law in several Muslim-majority countries is implemented in various ways, such as strict and overall, flexible, gradual, developing, or only applied in certain cases.